Determinants of quality of life among adolescents with irritable bowel syndrome symptoms (Nursing and Health Sciences Journal (NHSJ), 2025)
Irritable Bowel Syndrome (IBS) can harm the quality of life, social, economic, and psychological aspects. The declining quality of life of adolescents with IBS will have a significant effect on the next stage of life. This study aims to identify the determinants of quality of life in adolescents with irritable bowel syndrome (IBS) symptoms in public senior high schools. The design of this study was a cross-sectional study with a sample size of 344 adolescents selected by consecutive sampling. Data collection employed self-report instruments, including demographic characteristics, the IBS Symptom Severity Score (IBS-SSS), the Big Five Inventory (BFI-10), the Hopkins Symptom Checklist (HSCL-25), the Patient Health Questionnaire (PHQ-15), and the Irritable Bowel Syndrome Quality of Life (IBS-QOL) scale. A multivariate analysis using multiple logistic regression shows a significant relationship between the severity of IBS symptoms, psychological distress, and somatic symptoms on the quality of life of adolescents with IBS symptoms (p-value < 0.001; < 0.001; < 0.001). From the results of the final modeling using multiple logistic regression, it is evident that somatic symptoms are the most influential determinant of the quality of life of adolescents with symptoms of IBS, with an Odds Ratio (OR) value of 0.620 (95% CI: 0.470-0.818). The Health Departments, health professionals, schools, and parents are encouraged to collaborate in designing consultation, education, intervention, and evaluation programs to manage IBS and somatic symptoms experienced by adolescents.